Perceived greenwashing and its impact on eco-friendly product purchase - Alireza Shabani shojaei; Belem Barbosa; Zaila Oliveira (Tourism & Management Studies)
Notwithstanding the increasing commitment of managers toward environmental sustainability, consumer skepticism remains widespread, often resulting in perceptions of greenwashing. Although greenwashing has been studied by researchers, there is a lack of understanding of how consumers' Perceived greenwashing affects their consumption behavior. The current study aims to investigate how perceived greenwashing impacts consumers’ purchasing behavior of environmentally friendly products. The study used the “theory of planned behavior” and the “theory of perceived risk”. For data analysis, SmartPLS3 was employed. Results confirm that the perceived greenwashing leads to a decrease in the attitude, purchase intention, and purchase behavior of eco-friendly products. Both perceived risk and perceived differentiation also were found to influence purchase intention. These findings confirm the negative impact of greenwashing perception on consumer behavior and highlight the need for transparency and clear environmental claims in product communication.